A family stress approach to understanding sibling relationships following parental divorce - Wilkins-Clark, Renée Elizabeth (Kansas State University, 2019)
This study utilized a family stress theory perspective to examine differences between young adults with married parents and those who experienced parental divorce and whether or not levels of perceived sibling support and perceptions of experiential discrepancy influence sibling relationship closeness following parental divorce. The sample was recruited using Amazon Mechanical Turk and consisted of young adults who experienced parental divorce, had continuously married parents, and had at least one, living, biological sibling. Participants who experienced parental divorce (N=107) were asked to report on the biological sibling that they felt closest to before their parents’ divorce, while participants with married parents (N=197) were asked to report on the sibling that they felt closest to. The data were examined using paired-sample t-tests, independent samples t-tests, and multiple linear regression analysis. Significant differences were found for sibling relationship closeness and the affect dimension of relationship closeness for those with married parents. Significant differences were also found for the dimension of behavior, for those who experienced parental divorce. Experiential discrepancy was found be a significant indicator of sibling relationship closeness before the inclusion of the support variables and success of support seeking was found to be a significant predictor of sibling relationship closeness following parental divorce. The implications of the results will be discussed along with future directions.
Keywords: Parental divorce; Family stress theorySiblings